Cascading effects of benthic fish impede reinstatement of clear water conditions in lakes: A mesocosm study. (1st January 2022) - Ren, Wenjing; Wen, Zihao; Cao, Yu; Wang, Hao; Yuan, Changbo; Zhang, Xiaolin; Ni, Leyi; Xie, Ping; Cao, Te; Li, Kuanyi; Jeppesen, Erik
Abstract: In shallow eutrophic lakes, submersed macrophytes are essential for maintaining a clear water state, and they are affected markedly by fishes directly through herbivory and indirectly by fish-invertebrate-periphyton complexity, a pathway that presently is not well understood in subtropical lakes but probably vital to lake managements. We conducted a mesocosm study involving benthic fish ( Misgurnus anguillicaudatus ), snails ( Radix swinhoei ) and submersed macrophyte ( Vallisneria natans ), aiming to examine whether benthic fish is detrimental to reestablishment of clear-water macrophyte-dominated state in eutrophic degraded lakes. In addition, we aimed to investigate the cascading effect that benthic fish might have on periphyton and phytoplankton and to what extent snails can alleviate this effect. Our results showed that benthic fish promoted nutrient release from the sediment and thereby facilitated the growth of phytoplankton and periphyton, leading to reduced growth of submerged macrophytes due to shading. Snails consumed the periphyton attached on the leaves of macrophytes, thereby being beneficial to the plant growth, albeit it could not fully counteract the adverse effects from benthic fish. The water quality indicators in terms of nutrients concentrations, phytoplankton biomass and light extinction coefficient along the water column was affected primarily by benthic fish, followed by macrophytes and snails. To target a clear-water condition, the water quality was best at the presence of macrophytes alone or in combination with snails, and worst at the presence of benthic fish. Our results implied that the removal of benthic fish should be a useful ecological restoration method for rehabilitation of submersed macrophytes and water quality improvement in subtropic, eutrophic, shallow lakes following external nutrient loading reduction. Graphical abstract: Image 1 Highlights: Benthic fish increased phytoplankton and periphyton, decreased biomass of macrophytes. Snails enhanced macrophyte growth, but cannot completely counteract negative effects of benthic fish. The nutrients utilization ratio of phytoplankton was enhanced by benthic fish. Benthic fish ultimately altered the community structure among three primary producers.